Climate change impacts on the future offshore wind energy resource in China. (September 2021) - Costoya, X.; deCastro, M.; Carvalho, D.; Feng, Z.; Gómez-Gesteira, M.
Abstract: Chinese offshore wind energy sector is experiencing a rapid growth. It is expected that China will become the world leader in terms of installed offshore wind energy capacity in the upcoming years. A multi-model ensemble of eight simulations from CORDEX project was considered to evaluate future offshore wind energy projections along the Chinese coast under the RCP8.5 warming scenario. Furthermore, offshore wind energy resource was classified attending to the richness of the resource, stability of the resource, risk and economic factors. The reliability of the CORDEX multi-model ensemble was analyzed by comparing CORDEX wind speed with two different datasets: in-situ data from oceanic buoys and ERA5 database. A general wind power density decrease was observed for the near future and the far future. At seasonal scale, differences were found depending on the season. Thus, a clear reduction was projected during spring, whilst increases were observed in wide areas during winter or autumn. Regarding the classification of the future offshore wind energy resource for the upcoming decades, most of the Chinese coastal area was defined as good or excellent due to its high offshore wind energy richness that compensate the low values on stability of the resource and risk factor.